Getting Irish Youth on the Job Track - González Pandiella, Alberto (OECD Publishing, 2013)
Irish youth was hit hard by the crisis. Many young workers have remained unemployed for a long time and, unless it is tackled promptly, this issue will become one of the most enduring legacies of the recession. New labourmarket policy initiatives have been introduced recently, but more will be needed to limit scarring effects and keep youth connected so that they can get back to work as soon as the recovery strengthens. For many young workers learning new skills is the way to get ready. The Irish economy is shifting away from bricks and mortar towards knowledge-based services, and those previously employed in construction-related activities need to acquire the skills and competencies required in these expanding sectors. For those who have already drifted into more marginalised environments, a longer process of rehabilitation will be necessary to escape poverty and social exclusion. This chapter recommends focusing limited fiscal resources on policies empirically-proven to help regain employment; this will require systematic and rigorous evaluation of labour-market programmes and policy decisions to close down ineffective schemes while strengthening successful ones
Keywords: Employment; Economics; Ireland